Core–shell Cd0.2Zn0.8S@BiOX (X = Cl, Br and I) microspheres: a family of hetero-structured catalysts with adjustable bandgaps, enhanced stability and photocatalytic performance under visible light irradiation. Issue 35 (11th August 2016) - Zhou, Yannan; Wen, Ting; Chang, Binbin; Yang, Baocheng; Wang, Yonggang
Abstract : Core–shell Cd0.2 Zn0.8 S@BiOX microspheres with tunable bandgaps, enhanced stability and photocatalytic activity were fabricated via a facile solvothermal route. Abstract : Heterostructures consisting of two semiconductors have merited considerable attention in photocatalytic applications due to synergistic effects in complex redox processes. The incorporation of solid solutions into such architectures can further offer extra variability to control the bandgap. In this study, we report the fabrication of a series of core–shell Cd0.2 Zn0.8 S@BiOX (X = Cl, Br and I) microspheres via a solvothermal route that lead to enhanced photocatalytic performance under visible light irradiation. By optimizing the synthesis conditions, uniform and porous Cd0.2 Zn0.8 S@BiOX microspheres were achieved. The products were thoroughly characterized by X-ray diffraction studies, scanning electron microscopy, transmission electron microscopy, photoluminescence studies, absorption measurements and the photodegradation of RhB. Remarkably, the electronic structures of Cd0.2 Zn0.8 S@BiOX composites can be continuously tuned by varying the composition of BiOX to achieve the best catalytic performance under visible light irradiation. Finally, this greatly enhanced visible-light-driven photocatalytic efficiency was observed in the optimized Cd0.2 Zn0.8 S@BiOI composites when compared to their single-component counterparts, which may be attributed to increased light absorption and improved electron–hole separation. The photocatalytic mechanism has also been proposed based on the experimental evidences and the theoretical band positions of Cd0.2 Zn0.8 S@BiOI.